Pengaruh Diet Protein Kedelai terhadap Profil Lipida Tikus Diabetik Induksi Alloxan - Ni Wayan Wisaniyasa; Yustinus Marsono; Zuheid Noor (agriTECH, 2005)
Hypolipidemic of soybean protein were evaluated in alloxan-induced diabetic rats. The objectives of this research were to evaluate the effects of soybean protein feeding on total, HDL, LDL cholesterol and triacylglycerol serum level in both normal cholesterol and hypercholesterol alloxan-induced diabetic rats. Twenty-eight male Sprague-Dawley rats (250-300 g) were used and divided into four groups of seven rats. They were (1) Standard-Placebo (STP), (2) StandardAlloxan (STA), Soybean protein-Alloxan (PKA) and (4) Soybean protein- Hypercholesterol-Alloxan (PKHKA) groups. Three groups were diabetic induced by alloxan injection (80 mg/Kg of body weight by intra-muscular injection) and one group was injected with aquabidest (Placebo). PKHKA group was fed hypercholesterol diet for 2 weeks prior to the alloxan injection. STP and STA groups were fed standard diet whereas PKA and PKHKA were fed soybean protein diet for 28 days. Concentration of lipids were determined before injection (0 day ) and 1, 7, 14, 21, and 28 days after injection. It was found that alloxan injection increased serum total and LDL cholesterol and triacylglycerol concentration of STA, PKA and PKHKA rats. In 28 days intervention, soybean protein diet decreased the serum total cholesterol by 12% (PKA) and 33% (PKHKA), LDL cholesterol by 15% (PKA) and 48% (PKHKA); and triacylglycerol by 31% (PKA) and 37% (PKHKA). In addition, the diet increased the serum HDL cholesterol by 3% (PKA) and 8% (PKHKA). On the other hand, standard diets were failed to decreased the serum total cholesterol, LDL cholesterol and triacylglycerol.